The Inability School Operational Assistance Fund in Remote Areas: Impact? - Ahmadnor, Ahmadnor (International Journal of Southeast Asian Studies (IJSAS), 2023)
The scope of provision of regional school operational assistance funds includes the provision of funds for public/private elementary schools, public/private Ibtidaiyah madrasahs, public/private junior high schools, and public/private Tsanawiyah madrasahs. The approach that will be used in this study is a qualitative approach because the researcher wants to produce conclusions in the form of data that describes in detail about phenomena that occur in the field. this research is through data analysis of Miles and Huberman's interactive model. The results showed the inability of Regional School Operational Assistance in terms of absorption and disbursement in schools in remote areas due to classical factors in aspects of communication, resources, disposition and bureaucratic structure. Schools in remote areas cannot absorb or disburse the Regional School Assistance Operational Fund to support school activities.